Capacitive Soot Sensor. (2015) - Hagen, G.; Rieß, G.; Schubert, M.; Feulner, M.; Müller, A.; Brüggemann, D.; Moos, R.
Abstract: A capacitive soot sensor was built up on basis of a known resistive device by covering the electrode area with a thin but dense alumina layer manufactured by the aerosol-deposition-method (ADM). Deposited soot cannot short-circuit the electrodes but leads to an increasing capacitance of the sensor. Experiments were conducted in real exhaust. Increasing soot concentrations lead to a more fast and sharp increase of the capacitance and the blind time of the sensor decreased to almost zero. The performance of such sensors could be enhanced when a voltage is applied at the electrodes during soot collection.